2010
DOI: 10.1103/physrevlett.104.252501
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Charge Equilibration Leading to the Synthesis of Exotic Nuclei

Abstract: Charge equilibration between two colliding nuclei can take place in the early stage of heavy-ion collisions. A basic mechanism of charge equilibration is presented in terms of the extension of singleparticle motion from one nucleus to the other, from which the upper energy-limit of the bombarding energy is introduced for significant charge equilibration at the early stage of the collision. The formula for this limit is presented, and is compared to various experimental data. It is examined also by comparison t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 28 publications
1
66
0
Order By: Relevance
“…In fact, the probability P (N, Z) to have a fragment with Z and N , in TDHF calculations, is the product of the probabilities P (Z)P (N ) to have Z and N , independently [23]. For instance, in the symmetric collisions studied here, the TDHF probability to have the N = Z 32 S nucleus is the same as for the neutron rich 40 S. The latter should, however, be hindered by the symmetry energy which induces a fast charge equilibration in the fragments [29]. Such effect is included in the BV approach which give σ N Z ≃ σ ZZ in damped collisions, while, in quasi-elastic reactions, correlations are negligible compared to fluctuations [see Fig.…”
mentioning
confidence: 97%
“…In fact, the probability P (N, Z) to have a fragment with Z and N , in TDHF calculations, is the product of the probabilities P (Z)P (N ) to have Z and N , independently [23]. For instance, in the symmetric collisions studied here, the TDHF probability to have the N = Z 32 S nucleus is the same as for the neutron rich 40 S. The latter should, however, be hindered by the symmetry energy which induces a fast charge equilibration in the fragments [29]. Such effect is included in the BV approach which give σ N Z ≃ σ ZZ in damped collisions, while, in quasi-elastic reactions, correlations are negligible compared to fluctuations [see Fig.…”
mentioning
confidence: 97%
“…These limitations turned out to be a hindrance for the development [16]. With the upgrade of computer power, three-dimensional TDHF simulation with full Skyrme effective interaction becomes possible and revived the new interests in nuclear dynamics as seen from an impressive series of recent publications [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Recent TDHF studies have been performed to investigate the charge equilibration in deep-inelastic collisions [46,48] and its impact on the interplay between fusion and transfer reactions [49][50][51][52][53][54]. Recent investigations have also shown that the one-body dissipation mechanisms included in TDHF were the most relevant to describe fully damped reactions such as quasi-fission [55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%